Professional Quality of Life for Psychiatric Nurses in Saudi Arabia - Aloufi, Abdulrahman Abed (Journal of Posthumanism, 2025)
This systematic review investigates the professional quality of life (ProQoL) among psychiatric nurses in Saudi Arabia, focusing on three central dimensions: Compassion Satisfaction (CS), Burnout (BO), and Secondary Traumatic Stress (STS). With the growing demands on mental health services and the unique occupational challenges psychiatric nurses face, understanding the variables influencing their well-being has become critical for healthcare sustainability and staff retention. A thematic meta-synthesis was conducted on fifty peer-reviewed studies published between 2019 and 2024. Inclusion criteria were limited to studies focused exclusively on psychiatric nurses working in Saudi Arabia, utilizing validated instruments such as the ProQoL Scale and Maslach Burnout Inventory. The analysis categorized findings thematically and synthesized statistical outcomes including Pearson correlations and regression models to examine ProQoL predictors. The results reveal that CS is positively associated with institutional support, participatory leadership, and resilience training. In contrast, BO and STS are elevated in settings marked by high workload, role ambiguity, lack of supervision, and exposure to patient trauma. Temporal trends indicate that COVID-19 significantly intensified BO and STS while reducing CS, especially among early-career nurses. Notably, private institutions were more likely to report higher CS and lower BO, suggesting that organizational culture plays a pivotal role in shaping ProQoL outcomes. These findings underscore the urgent need for trauma-informed care frameworks, emotional safety protocols, and systemic reforms in public psychiatric institutions to improve nurses’ well-being and enhance the quality of mental health services.